The Role of Leukotrienes in the Development of Broncho-Obstructive Syndrome - Ye.I. Yulish; O.Ye. Chernyshеva; A.S. Tyurina; V.S. Kolesnikova (Zaslavsky O.Yu., 2013)
This article describes the mechanism of action of leukotrienes in broncho-obstructive syndrome, including bronchial asthma in children.